ECONOMIC AND LEGAL BASIS OF TAX COLLECTION MECHANISMS FROM INDIVIDUALS IN THE PROCESS OF TAX ADMINISTRATION (World Bulletin of Management and Law, 2026)
This article provides a comprehensive analysis of the issues of improving the economic and legal foundations of tax collection mechanisms from individuals in the process of tax administration. The study highlights the institutional factors of ensuring full coverage of the tax base and the stability of revenues in the context of diversification of incomes of individuals, expansion of new forms of business activity, such as digital services and freelance. The scientific analysis evaluates approaches such as electronic tax services, automated control tools, integration of information exchange, and strengthening control based on risk models from the point of view of tax discipline and reducing the share of the shadow economy. In addition, a comparative analysis of international experience and national practice is carried out, and practical proposals are put forward to protect taxpayers' rights, increase accounting transparency, and institutionally strengthen state-citizen tax relations. The conclusions of the article substantiate the possibility of increasing the stability of budget revenues by deepening the digitization of tax administration, harmonizing data registers, and introducing intelligent models of control